2016
DOI: 10.1590/1980-5373-mr-2016-0009
|View full text |Cite
|
Sign up to set email alerts
|

Novel Ag3PO4/CeO2 p-n Hierarchical Heterojunction with Enhanced Photocatalytic Performance

Abstract: The composite Ag 3 PO 4 /CeO 2 photocatlyst, a novel p-n type heterojunction, has been successfully fabricated through a facile hydrothermal process combined with a successive in situ precipitation technique. The X-ray diffraction (XRD), scanning electron microscopy (SEM), high-resolution transmission electron microscopy (HRTEM) and UV-visible diffuse reflectance spectra (DRS) were used to characterize the as-obtained products. The SEM and TEM image show that CeO 2 particles have been successfully loaded and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…The peaks at 2 θ = 21.1°, 29.6°, 33.1°, 36.5°, 47.7°, 52.3°, 57.4°, 61.5° and 71.4° were due to Ag 3 PO 4 (Fig. b) in addition to peaks due to MOF‐5 …”
Section: Resultsmentioning
confidence: 95%
“…The peaks at 2 θ = 21.1°, 29.6°, 33.1°, 36.5°, 47.7°, 52.3°, 57.4°, 61.5° and 71.4° were due to Ag 3 PO 4 (Fig. b) in addition to peaks due to MOF‐5 …”
Section: Resultsmentioning
confidence: 95%
“…This establishes an internal electric field across the p-n junction. These electrostatic forces result in effective separation of charge carriers, thereby reducing the recombination rate and improving the catalytic performance [66]. Well-known p-n junction-based degradation mechanisms are listed in Table 7.…”
Section: P-n Junctionsmentioning
confidence: 99%
“…From the spectra of pure Ag 3 PO 4 nanoparticles and the Ag 3 PO 4 /Ag nanocomposite, it can be observed that two samples exhibited the similar emission peaks in the visible-light range. The strong emission around 420 nm is supposed to arise from the recombination of the charge-transfer transition between the O2p orbital and the empty d orbital of the central Ag + or of the self-trap excitons in the PO 4 oxyanion complex 17 . The broad PL band centered at 500 nm is considered to originate from the radiative recombination of photo-generated holes with electrons around the surface oxygen vacancy.…”
Section: Resultsmentioning
confidence: 99%